Middle School Students' Free-living Physical Activity on Physical Education Days, Non-physical Education Days, and Weekends - Risto Marttinen; Ray N. Fredrick III; Stephen S. Silverman (Montenegrin Sports Academy, 2018)
This study measured students' free-living Physical Activity (PA) in order to examine activity patterns of youth. Students (N=221) in 12-classes wore accelerometers to measure their PA over six weeks in and out-of-school while participating in a fitness unit. PA was significantly higher during Non-PE-Days and PE-Days than on Sundays. PA was significantly higher during baseline than weeks five and six. There were no significant differences between boys and girls in the number steps taken. Eighth-grade students had the lowest PA levels. On average, the students were attaining 60 minutes of MVPA. Students, however, did not often reach national recommendations. Girls reached their national recommendations five out of six weeks on days that they participated in PE. The results suggest that specific subgroups, such as adolescent girls, are getting the recommended PA but only when the PA is structured. A spike in PA during the first week suggested a possible motivational effect of the accelerometer.